Human security and peacebuilding through a gender lens: Challenges of implementation in Africa - Heidi Hudson (Danish Institute for International Studies (DIIS), 2006)
Empirical evidence shows that while both women's near absence at the formal level as peace negotiators and political decision-makers and their informal peacebuilding contributions at the grassroots level have been routinely recognised, it remains difficult to translate gender awareness into workable plans for implementation. The paper argues for a hybrid position between cultural relativism and `one size fits all' solutions. Four areas of attention are highlighted, namely women's ambivalent roles in peace and conflict, the challenges of a truly inclusive post-conflict transformation process, the need for an organised women's movement, and connecting the international legislative framework with the national context.
Keywords: 330; Frauen; Gleichberechtigung; Entwicklung; Friedenssicherung; Afrika